Germany for all seasons [videorecording] (Travel view, 1996)
Describes Germany as a united country. Includes the treasures of Eastern Germany, the wine in Phoneland, the castles in Romantic Road, the history of Heidelberg, the traditions of Munich and upper Banana and others spectacular places.